2020
DOI: 10.1523/jneurosci.0724-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Mesolimbic Dopamine Activity Signatures of Relapse to Alcohol-Seeking

Abstract: The mesolimbic dopamine system comprises distinct compartments supporting different functions in learning and motivation. Less well understood is how complex addiction-related behaviors emerge from activity patterns across these compartments. Here we show how different forms of relapse to alcohol-seeking in male rats are assembled from activity across the VTA and the nucleus accumbens. First, we used chemogenetic approaches to show a causal role for VTA TH neurons in two forms of relapse to alcohol-seeking: re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 76 publications
0
50
0
3
Order By: Relevance
“…Whole-cell patch-clamp recordings from made from eNpHR3.0-expressing VTA neurons in vitro from TH::Cre+ rats to confirm the inhibitory nature of the photostimulation and its effectiveness across the durations to be used in later behavioral experiments ( Figure 1A,B). We have previously reported that eNpHR3.0 expression is specific to VTA TH+ neurons in this rat line (Liu et al, 2020). The recorded neurons (12 neurons from 3 rats)…”
Section: Experiments 1: Photoinhibition Of Vta Dopamine Neuronsmentioning
confidence: 95%
See 1 more Smart Citation
“…Whole-cell patch-clamp recordings from made from eNpHR3.0-expressing VTA neurons in vitro from TH::Cre+ rats to confirm the inhibitory nature of the photostimulation and its effectiveness across the durations to be used in later behavioral experiments ( Figure 1A,B). We have previously reported that eNpHR3.0 expression is specific to VTA TH+ neurons in this rat line (Liu et al, 2020). The recorded neurons (12 neurons from 3 rats)…”
Section: Experiments 1: Photoinhibition Of Vta Dopamine Neuronsmentioning
confidence: 95%
“…We have previously shown that Cre−dependent AAV expression is limited to TH+ neurons in the VTA of the TH-Cre rat (Liu et al, 2020). Here eYFP and mCherry labelling was detected using single-colour peroxidase immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…They found that inactivation of the prelimbic cortex reduced contextual renewal but increased responding during reacquisition [60]. These neurobiological differences were recently extended to the pattern of activation in the mesolimbic dopamine system, such as the medial ventral tegmental area, which was required for reacquisition but not renewal [61]. While rapid reacquisition is generally an underutilised paradigm in drug self-administration studies [62], these neurobiological findings indicate that contextual renewal and rapid reacquisition are dissociable, suggesting that mechanisms other than renewal contribute to rapid reacquisition.…”
Section: Rapid Reacquisitionmentioning
confidence: 97%
“…To be sure, activity in VTA dopamine neurons is important for relapse. VTA dopamine neuron activity is obligatory for cue-induced reinstatement of cocaine-seeking (Mahler et al, 2014) as well as cue (Valyear et al, 2020) and context-induced reinstatement of alcohol-seeking (Liu et al, 2020) because chemogenetic inhibition of these neurons prevents these forms of relapse. However, although important because they causally link reinstatement to the activity of VTA dopamine neurons, these kinds of global manipulations of VTA dopamine neurons obscure important findings.…”
Section: Ta Comple Xitie Smentioning
confidence: 99%